Fire Performance of FRCM-Confined RC Columns: Experimental Investigation and Parametric Analysis - Reem Talo; Salem Khalaf; Farid Abed; Ahmed El Refai (Composites Part C: Open Access)
This study presents an experimental investigation of the fire response of six columns strengthened with polyparaphenylene benzobisoxazole (PBO) FRCM system, and tested in a large-scale furnace following ASTM E119 standards. The parameters investigated included the number of PBO-FRCM layers and the presence of a fireproofing insulation layer. Test results highlighted the effectiveness of PBO-FRCM in insulating the column, with the strengthened column showing a substantial 31.9% reduction in temperature readings at the concrete surface compared to its unstrengthened counterpart. Furthermore, the presence of Sikacrete 213F fireproofing system reduced temperature readings within the column's section by an average of 65%. Based on the experimental results, a parametric numerical study were developed and verified using ABAQUS software. The parameters studied included the number of PBO-FRCM layers (0, 1, and 2 layers), the presence of a 30 mm thick insulation layer, and the axial preloading taken as 40, 60, and 75% of the ultimate column's capacity. The model accurately predicted the temperature readings across the columns. Strengthening the columns with PBO-FRCM significantly increased their resistance during fire, doubling fire-resistance duration with one layer. Adding fireproof insulation led to significant increase in load resistance duration. The percentage drop in temperature after 1 hour of fire exposure was around 70% at the FRCM surface for the insulated column strengthened with one layer of FRCM. Higher preload percentages reduced both the fire-resistance duration and ductility of the columns. For the group of columns strengthened with one layer, increasing the preloading percentage to 60% and 75% resulted in decreases in the fire-resistance duration of 35% and 73%, respectively.